Correlation between empathy and academic performance in university students - Callupe-Becerra, Sonia F. (2019)
The aim of the research is to correlate the empathy with the academic performance obtained by the students of the Specialty of Primary Education, Faculty of Education Sciences of the Hermilio Valdizán University of the city of Huánuco in the period 2017-I. Method. A correlational descriptive study was conducted with 128 students enrolled in the 2017-I semester in the Vocational School of Primary Edu- cation. Results and conclusions. There is no significant relationship between academic performance and empathy in students, the Pearson correlation coefficient between both variables is -.043 and bilat- eral significance of .628. The variable empathy was worked on in four dimensions: taking perspective, fantasy, taking perspective and personal discomfort. There is no significant relationship between aca- demic performance and perspective taking dimension, we obtained a Pearson correlation coefficient of.053 and bilateral significance of .552. There is no significant relationship between academic perfor- mance and the fantasy dimension, Pearson correlation coefficient of -060 and bilateral significance of.501. There is no significant relationship between academic performance and the empathic concern dimension, a Pearson correlation coefficient of -126 and significance of .208 was obtained, there is no significant relationship between academic performance and the personal discomfort dimension, a correlation coefficient was obtained of Pearson of .015 and bilateral significance of .871.